Occlusal dysesthesia: a topical narrative review. (21st May 2015) - Melis, M.; Zawawi, K. H.
Summary: Occlusal dysesthesia (OD) is a disorder characterised by the sensation of uncomfortable bite with no obvious occlusal discrepancy. It is usually associated with emotional distress and is elicited by dental occlusal procedures. Multiple dental treatments are often provided to try to resolve the symptoms, but the outcome is usually dissatisfying for the dentist and disappointing for the patient. To summarise the specific features of OD, a PubMed search was carried out looking for all papers related to the topic. The references from the studies selected and from review articles were also examined for further relevant papers. A total of 138 articles were first identified, of which 18 of them were considered relevant to the topic. This article reviews the epidemiology, taxonomy and etio‐pathophysiology, symptomatology, diagnosis and treatment of OD, with special relevance to issues of clinical importance and dental therapy. Any dental treatment must be avoided in patients with OD, because the results could be inadequate and it usually worsens the symptoms.